Mapas para desorientar e territorializar ambientes e corpos - Genioli, Ana Amélia Corazza (2014)
The main objective of the research is to analyze communicative actions that explore different relationships between body and environment through performative experiments. The corpus of the research is composed of artistic works by Jorge Macchi, Lee Ufan and Silvia Bächli. Acting on different continents (Latin America, Asia and Europe), these creators have checked the epistemological boundaries between art and communication; instead of dealing with materials and aesthetic models, they focus on exploring communicative relationships between body and environment, essentially starting from perception processes. To do so, they have been building cognitive cartography that reinvent cities and objects, desecrating the role of the individual as sovereign agent of communication processes. The central hypothesis of the thesis is that, from specific strategies that translate images, maps and actions in concepts, the experiences analyzed showed the resistance paths to models of subordination, destabilizing previously known identity categories and classifications, in which the subjects usually recognize themselves. The theoretical basis is given by the bodymedia theory (Greiner and Katz) , which triggers a network of authors from several areas such as theories of communication, cognitive science and political philosophy, in order to analyze in a complex and non-deterministic way the constitution of subjectivities. The result presented is not restricted to the analysis of works, but seeks to work with broader issues in the field of communication, especially in its political developments, more and more explicit in recognizing the entire body as bodymedia